Manic Symptoms during a Switch from Paliperidone ER to Paliperidone Palmitate in a Patient with Schizophrenia - Demirci, Kadir; Keleş, Süleyman; Demirdaş, Arif; Korucu, Cafer Çağrı (Case Reports in Psychiatry, 2015)
Some antipsychotic drugs have treatment efficacy for mania and bipolar disorder. However, these drugs may rarely cause manic symptoms in some schizophrenic patients. We hereby report a 22-year-old female patient with schizophrenia who experienced a manic episode during a switch from paliperidone ER to paliperidone palmitate. This case is an important reminder that an abrupt switch from oral paliperidone to paliperidone palmitate may predispose certain patients to hypomanic or manic symptoms.